Manipulação de objetos 3D em ambientes colaborativos com o uso do dispositivo Kinect - Silveira Junior, Wedson Gomes da (2013)
The research on natural interaction has been growing significantly since, with the spread of personal computers, there is an increasing demand for interfaces that maximize productivity. Among these we can highlight the interfaces Virtual Reality and Augmented Reality (KIRNER, TORI e SISCOUTO, 2006), where users can perform simple tasks such as choosing a 3D object translation, rotation and scaling in 3D object. These tasks are usually performed through devices such as the keyboard and mouse, and can, thus, a loss of immersion happen by the user in the virtual environment. Thus, investigating methodologies for natural interaction in these environments, can help increase user immersion in the virtual environment. Another issue that have been the focus of many researches are Collaborative Virtual Environments (KIRNER e TORI, 2004), where it is possible for users to communicate and share information. These users can be physically close or not. The main focus of this work is precisely the communication among remotely dispersed users. Thus, it is intended with this work, proposing a system where it is possible to manipulate 3D objects using natural gestures and share data remotely dispersed users.